A case study of residential buildings subjected to cracking failures - Jamaluddin, Norwati; Yeoh, David; Abdul Ghani, Abdul Halim; Koh, Heng Boon; Shah Ayob, Sallehudin; Wan Ibrahim, Mohd Haziman; Mohamad, Noridah; Tuan Chik, Tuan Norhayati; Abd. Ghafar, Nor Hayati (Penerbit UTHM, 2018)
The purpose of this paper is to present some preliminary findings of residential buildings which subjected to cracks. The study case covered in this paper is to determine the cause of cracking of semi-detached residential houses which initially expected due to a construction project nearby. Several types of buildings and infrastructures were evaluated through the preliminary qualitative forensic assessment for the hypothesis on the cause of the problems on residential buildings. The initial assumption that caused the cracking was due to the nearby construction works. From the inspection it was suggested that the piling work from the construction project does not have an impact that could damage or jeopardize the main structures. It was expected that the failures occurred on the walls and floors of the houses are more reflected due to the soil settlement on the housing area.